Analisis Penerapan Sistem Akuntansi Persediaan Barang Dagangan Dengan Menggunakan Metode FIFO Pada PT. Primajaya Multy Technology - Muhammad Affandy Tampubolon; Zufrizal Zufrizal; Farida Khairani Lubis; Lusi Elviani Rangkuti (Universitas Islam Islam Sumatera Utara, 2022)
The objectives to be achieved in this study are to analyze the application of the merchandise inventory accounting system using the FIFO method where the object of the company to be studied is PT Primajaya Multy Technology. This study uses a qualitative descriptive research method. Data obtained through observation, interviews, and documentation. Based on the results of research on the application of the merchandise inventory accounting system at PT. Primajaya Multy Technology, the authors can draw the following conclusions: The merchandise inventory accounting system at PT Primajaya Multy Technology has not been effective where there is no segregation of duties between divisions, where each division can manage and enter the work of other divisions in the work, while inventory recording uses the perpetual method, with a computerized system so that the company can find out the amount of inventory available at any time, because the inventory records are able to present data from every transaction of entry and expenditure of goods completely and accurately. The use of this system is quite effective by looking at the many types of inventory sold. So it requires a recording system that can always provide an information system about inventory both from the number of units, the cost per unit, and the total value of the inventory held. The method for inventory valuation is also appropriate, by choosing the FIFO method where the goods that enter first will be issued or sold first so that the last purchased goods can be avoided from obsolescence and missed return dates set by the vendor. The procedures that make up the merchandise inventory system are good enough where every goods release or borrowing of goods from the warehouse is accompanied by a TTBG (receipt of goods from the warehouse) where the receipt is proof that the goods have been taken from the warehouse by who took it